Kant and Kierkegaard on Religion
XXI, 303 p.
Keywords: The contributions of leading Kantian and Kierkegaardian scholars to this collection break down to the simplistic contrast in which Kant is seen as the advocate of a rational moral theology and Kierkegaard as the advocate of an irrationalist faith. This collection is an ideal text for discussion of central issues.